Intrapulmonary (i.pulmon.) Pull Immunization With the Tuberculosis Subunit Vaccine Candidate H56/CAF01 After Intramuscular (i.m.) Priming Elicits a Distinct Innate Myeloid Response and Activation of Antigen-Presenting Cells Than i.m. or i.pulmon. Prime Immunization Alone - Thakur, Aneesh; Pinto, Fernanda Endringer; Hansen, Harald Severin; Andersen, Peter; Christensen, Dennis; Janfelt, Christian; Foged, Camilla (Frontiers in Immunology, 2020)
Understanding the in vivo fate of vaccine antigens and adjuvants and their safety is crucial for the rational design of mucosal subunit vaccines. Prime and pull vaccination using the T helper 17-inducing adjuvant CAF01 administered parenterally and mucosally, respectively, has previously been suggested as a promising strategy to redirect immunity to mucosal tissues. Recently, we reported a promising tuberculosis (TB) vaccination strategy comprising of parenteral priming followed by intrapulmonary (i.pulmon.) mucosal pull immunization with the TB subunit vaccine candidate H56/CAF01, which resulted in the induction of lung-localized, H56-specific T cells and systemic as well as lung mucosal IgA responses. Here, we investigate the uptake of H56/CAF01 by mucosal and systemic innate myeloid cells, antigen-presenting cells (APCs), lung epithelial cells and endothelial cells in mice after parenteral prime combined with i.pulmon. pull immunization, and after parenteral or i.pulmon. prime immunization alone. We find that i.pulmon. pull immunization of mice with H56/CAF01, which are parenterally primed with H56/CAF01, substantially enhances vaccine uptake and presentation by pulmonary and splenic APCs, pulmonary endothelial cells and type I epithelial cells and induces stronger activation of dendritic cells in the lung-draining lymph nodes, compared with parenteral immunization alone, which suggests activation of both innate and memory responses. Using mass spectrometry imaging of lipid biomarkers, we further show that (i) airway mucosal immunization with H56/CAF01 neither induces apparent local tissue damage nor inflammation in the lungs, and (ii) the presence of CAF01 is accompanied by evidence of an altered phagocytic activity in alveolar macrophages, evident from co-localization of CAF01 with the biomarker bis(monoacylglycero)phosphate, which is expressed in the late endosomes and lysosomes of phagocytosing macrophages. Hence, our data demonstrate that innate myeloid responses differ after one and two immunizations, respectively, and the priming route and boosting route individually affect this outcome. These findings may have important implications for the design of mucosal vaccines intended for safe administration in the airways.